Determination of Continuance Intention on Learning Management Systems: Modification of the UTAUT Model with Social Isolation and Corona Fear - Hidayat, Wahyu; Sugandini, Dyah; Istanto, Yuni (Journal of International Conference Proceedings, 2022)
The COVID-19 pandemic requires students to study online using the Learning Management System (LMS). So studies are needed to understand students' continuing interest in adopting LMS during the COVID-19 pandemic by modifying the Unified Theory of Acceptance and Use of the Technology (UTAUT) Model. Modify this model by adding Social Isolation, Corona Fear, and Continuance Intention. This study used a quantitative method involving 310 student respondents using LMS in Yogyakarta using a simple random sampling technique. The questionnaires obtained were then processed using SEM-PLS analysis with the help of the SmartPLS version 3.2.9 statistical application. This study succeeded in finding that Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), and Facilitating Conditions (FC) had a positive and significant effect on Continuance Intention (CI). In contrast, Social Isolation (Iso) had a positive and unsignificant effect to CI. This study also found that the moderating effect of Corona Fear (CF) weakened the relationship between PE, SI, FC & SI on CI. In contrast, the moderating effect of CI strengthened the relationship between EE on CI. Based on the results of the exploratory study, it was found that it is likely that students will experience online learning saturation and want to study face-to-face immediately.Keywords: The UTAUT Model, Social Isolation, Corona Fear, Learning Management System, and the COVID-19 Pandemic.